LANGERHANS CELL HISTIOCYTOSIS IN CHILDREN - AL-JADIRY, MAZIN F.; AL-HADAD, SALMA A.; ABD, KHALID Q. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Langerhans cell histiocytosis (LCH) is a rare proliferative disorder of histiocytes encompasses a wide clinical spectrum, ranging from a benign localized disease to acutegeneralized disease with fatal outcome.Objectives: to retrospectively evaluate clinical characteristics at diagnosis and outcome of patients with Langerhans cell histiocytosis.Patients and methods: A retrospective analysis of data on 21 children with Langerhans cell histiocytosis followed at Oncology unit, Children Welfare Teaching Hospital, Medical City,Baghdad, between 1999 and 2006.Results : The age at time of diagnosis of LCH ranged from 3 months to 9 years, with a median of 22 months, and male to female ratio was 1:1.1. The duration of the onset of the disease before diagnosis ranged from 1month to1 year. Bone lesions, skin lesions and LAP were the common presenting features. Skull was the major site of lytic lesions 10(47.6%) patients. Tissue biopsy and/or aspiration were the main diagnostic procedures. Twenty patients treated by different combinations of chemotherapy. Ten patients survived (50%), and the mean time of follow up was 28 months.Conclusion : The study showed a relatively high incidence of advanced (III and IV) stages of disease 12 patients (57.1 %) with subsequent poor outcome and survival.Recommendation : Long term follow-up by a multidisciplinary care team is required